Gender, temporary work, and migration management : global food and utilitarian migration in Huelva, Spain - Zeneidi, Djemila (Palgrave Macmillan, 2020)
Contents: Gender, Temporary Work, and Migration Management; Series Editors' Foreword; Contents; List of Tables; 1 Introduction; The Feminization of Labour Migration; A Multi-Sited Investigation and an Approach Based on Recognition; Spaces, Domination, and Recognition; Notes; 2 "Global food" and Utilitarian Migration in Huelva; The Globalization of the Agricultural Economy; Eastern European Women Rather than African Men; Managing Migration at a Local Level; The Moroccan Partnership and European Funding Programmes; Cartaya as a Model for Labour Management; Notes; 3 Captive Bodies and Spatial Constraints. Contents: 5 False Recognition and Citizenship: The End of a DreamPossible Unemployment; The Humiliation of Being Deprived of Work; The Imminent Threat of Employment Termination; The Rejection of Not Being Called Back; The Pain of Being Sent Away Due to Pregnancy; Anger and Criticism; The Physical Effects of Being Discredited; Conflicting Identities; Space and Subjectivity; 6 Escaping the Management Apparatus: Running Away or Disappearing?; Necessary Alliances; Finding a Man: The Role of the Body in the Economy of Alliances; Preparing to Suffer; The Practical Dynamics of Transgression. Contents: Criticism and Moral DilemmasDisobedience as Moral Transgression; From Worker to Cyborg; Disobedience and Counter-Performativity; 7 Conclusion: Junk Space and Junk Workers; A Pilot Scheme; Outside Citizenship: The Ideal Worker; Bibliography; Index. Contents: Optimizing Means, Controlling Migration, Maintaining Efficient LabourControlling Behaviour, Bodies, and Living Spaces; Living Conditions and Work; Accommodation: Combining Confinement and Flexibility; Spatial Exclusion and Restricted Movement; Discipline and Fiction; Notes; 4 The Desire for Citizenship: Between Domination and Recognition; Oppressive Contracts and Strategic Subjection; Seeking Recognition from Employers; Coming to Terms with Domination; Lucid Consent; A Season of Hope and Trust; Escaping Constraints; The Valued Status of Breadwinner.